Formulasi dan Uji Stabilitas Hand Body Lotion dari Ekstrak Etanol Rumput Laut (Eucheuma cottonii) - Yusnita Usman (Journal Syifa Sciences and Clinical Research, 2022)
Research  has been carried out on formulation and stability test of hand body lotion from ethanolic extract of seaweed (Euchema cottonii). This study aims to obtain a hand body lotion formulation from seaweed extract (Eucheuma cottonii) that meets the requirements for the physical quality of the lotion, where the formula made consists of 4 formulas with extract concentrations of 5%, 10%, 15% and formulas without extracts. The evaluation of lotion preparations included organoleptic tests, pH tests, homogeneity tests and dispersibility tests. Data analysis was carried out by testing the physical quality of each formula compared to the quality standard of lotion preparations according to theory. From the research that has been done, it shows that the composition of the 4 formulas shows homogeneous results. The pH values of the formulas with extract concentrations of 5%, 10% and 5% and formulas without extracts were 5,8;5,3;5,1 and 6.6 (quality requirements 4,5 -6.6). Meanwhile, the pH distribution of the formula with 5%, 10% and 5% extract concentrations and the formula without extract was 5.2, respectively; 4.8; 4,4 and 5 (quality requirements 5-7). Based on the results obtained, it can be concluded that the formula with an extract concentration of 5% has the most physical stability that meets the requirements for the quality of lotion preparations.